How Delaying Fiscal Consolidation Affects the Present Value of GDP - Fletcher, Kevin (IMF Working Papers; Working Paper ;, 2015)
We develop a simple model to examine the conditions under which delaying fiscal consolidation can affect the present value of GDP via the fiscal stance's effects on the output gap and hysteresis. We find that the absolute size of the fiscal multiplier-the focus of much empirical investigation and policy debate-is likely inconsequential in this regard. Rather, what matters is the degree to which the multiplier during the initial period of fiscal stimulus differs from the multiplier when the stimulus is withdrawn. If the multiplier is constant over time, delaying consolidation is unlikely to significantly boost the present value of GDP via effects on the output gap and hysteresis. The potential success of such efforts relies instead on exploiting time-variation in multipliers.